1973
DOI: 10.1037/h0034430
|View full text |Cite
|
Sign up to set email alerts
|

The Amsel frustration effect: Interpretations and research.

Abstract: Experiments in the double runway and its analogs are reviewed and evaluated in terms of several theories that have been applied to this situation. Because of the complexity of the situation, a simple correspondence between the frustration effect (FE) and a hypothetical frustration response has not been convincingly demonstrated. Rather, a theoretical account of the FE must include possible effects of secondary reward, competing responses, generalization decrements, demotivation, and differential conditioning. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
17
0

Year Published

1975
1975
1989
1989

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 83 publications
2
17
0
Order By: Relevance
“…The frustration effect consisted of faster running in Alley 2 when the rat was not reinforced in the first goalbox. Scull (1973) has summarized the results of much of the research involving frustrative nonreinforcement.The first study specifically designed to investigate the effects of varied intervals of delay in a delay box on Alley 2 running speeds of rats that were never reinforced in the delay box was conducted by Holder, Marx, Holder, and Collier (1957). They observed that following training with a I-sec delay both the 15-sec and the 45-sec delay groups ran faster in Alley 2 than the l-sec delay group.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The frustration effect consisted of faster running in Alley 2 when the rat was not reinforced in the first goalbox. Scull (1973) has summarized the results of much of the research involving frustrative nonreinforcement.The first study specifically designed to investigate the effects of varied intervals of delay in a delay box on Alley 2 running speeds of rats that were never reinforced in the delay box was conducted by Holder, Marx, Holder, and Collier (1957). They observed that following training with a I-sec delay both the 15-sec and the 45-sec delay groups ran faster in Alley 2 than the l-sec delay group.…”
mentioning
confidence: 99%
“…The frustration effect consisted of faster running in Alley 2 when the rat was not reinforced in the first goalbox. Scull (1973) has summarized the results of much of the research involving frustrative nonreinforcement.…”
mentioning
confidence: 99%
“…The frustration effect consisted of faster running in A 2 when the rat was not reinforced in G,. Scull (1973) has recently summarized the results of much of the research involving frustrative nonreinforcement.A manipulation to which Brown and Farber (1951) attributed frustration eliciting properties, namely, introduction of a delay between the initiation and completion of a response sequence, has received very little attention. This neglect is especially perplexing since.…”
mentioning
confidence: 99%
“…The frustration effect consisted of faster running in A 2 when the rat was not reinforced in G,. Scull (1973) has recently summarized the results of much of the research involving frustrative nonreinforcement.…”
mentioning
confidence: 99%
“…runway performance). Scull (1973) has suggested that the double-alley runway may be a more complex situation than previously anticipated. The behavior of orienting to a startbox door, starting, and running is a relatively long instrumental chain, opportunity exists for the development of responses that compete with the dependent measure.…”
Section: U8mentioning
confidence: 91%